Novel Insights of Effects of Pregabalin on Neural Mechanisms of Intracortical Disinhibition in Physiopathology of Fibromyalgia: An Explanatory, Randomized, Double-Blind Crossover Study - Deitos, Alícia; Soldatelli, Matheus Dorigatti; Dussán-Sarria, Jairo Alberto; Souza, Andressa; da Silva Torres, Iraci Lucena; Fregni, Felipe; Caumo, Wolnei (Frontiers in Human Neuroscience, 2018)
Background: The fibromyalgia (FM) physiopathology involves an intracortical excitability/inhibition imbalance as measured by transcranial magnetic stimulation measures (TMS). The TMS measures provide an index that can help to understand how the basal neuronal plasticity state (i.e., levels of serum neurotrophins brain brain-derived neurotrophic factor (BDNF) and S100-B protein) could predict the effect of therapeutic approaches on the cortical circuitries. We used an experimental paradigm to evaluate if the pregabalin could be more effective than placebo to improve the disinhibition in the cortical circuitries in FM than in healthy subjects (HS). We compared the acute effect intra-groups of pregabalin with placebo in FM and healthy subjects (HS) in the current silent period (CSP) and short intracortical inhibition (SICI) (primary outcomes). Pain scores and pain pressure threshold (PPT) were secondary outcomes. Methods: This study included 27 women (17 FM and 10 HS), age range 19 to 65 years old. In a blinded, placebo-controlled, clinical trial, were randomized to receive in a cross-over manner oral pregabalin 150 mg or placebo. The cortical excitability pain measures were assessed before and 90 min after receiving the medication. Results: A generalized estimating equations (GEE) model revealed that in FM the pregabalin increased the CSP 14.34% [confidence interval (CI) 95%; 4.02 to 21.63] and the placebo reduced -1.58% (CI 95%; -57 to 25.9), (P=0.00). Pregabalin reduced the SICI -8.82% (CI 95%, -26 to 46.00) and the placebo increased 19.56% (CI 95%; 8.10 to 59.45; P=0.02). Also, the pregabalin improved the pain measures. Despite treatment group, the adjusted-BDNF index was positively correlated and the serum S100-B was negatively correlated with the CSP, respectively. However, in the HS the pregabalin and placebo not induced a statically significant effect neither in intracortical excitability nor pain measures. Conclusion: These results suggest that the pregabalin effect on cortical neural networks occurs particularly under basal neuronal hyperexcitability because its impact on the cortical excitability and in the pain measures was observed only FM group. They indicate that the pregabalin increased the CSP to induce inhibition in specific neural networks while it increased the SICI to improve the excitability in other neurobiological systems.